Los Uigur en la República Popular China (1949-2023). - Quintero González, Estefanny Alejandra; de Jesús Guerrero López, Oscar (Humania del Sur: Revista de Estudios Latinoamericanos, Africanos y Asiáticos)
The Uyghurs are an ethnic group that professes Islam, of Sunni current. Their dialect is of Turkish origin and their culture is very close to the peoples of Central Asia. They are settled in northwest China, specifically in the province of Xinjiang (officially Xinjiang Uyghur Autonomous Region), founded as an administrative subdivision of China in 1955. In this sense, the proposed article seeks to analyze the issue of the Uyghur ethnic group in the People's Republic of China from 1949 to 2023, based on the theoretical postulates of recent history and under the historical documentary method.